Herpes zoster fascialis sinistra on central vertigo patient suffering seizures after acyclovir oral administration: Neurotoxicity or coincidence? - Utomo, Thomas; Safruddin Amin; Anni Adriani; Dirmawati Kadir; Widyawati Djamaluddin; Asnawi Madjid (Journal of Pakistan Association of Dermatologists, 2023)
Herpes Zoster (HZ) is a painful dermatomal rash caused by reactivation of varicella-zoster virus in neuron cells. HZ affects all ages but it is more common in older and immunocompromised patients. Acyclovir is widely use to treat Herpes Zoster. Its water-solubility helps acyclovir metabolite, 9- carboxy methoxy methylguanine (CMMG) to penetrate cerebral fluid. A 33-year-old man with chief complaint of dizziness was diagnosed with central vertigo and underwent a Brain MRI. Two days before hospitalization, erythematous lesion, followed by painful zosteriform erythematous papules and vesicles, was seen on his left face, with noted malaise and appetite loss as prodromal symptoms. No cranial nerves were affected. Tzanck test revealed multinucleated giant cells due to infection. In general, laboratory results were normal, except for increased level of potassium (3 mmol/dl). Herpes Zoster Facialis Sinistra with maxillary branch involvement was diagnosed and oral acyclovir was given to the patient. Three hours after the first dose of acyclovir, convulsion was observed. The Acyclovir was discontinued, and wound therapy for the lesions was given with favorable outcomes. Brain MRI revealed many hyperintense lesions that were suggestive for toxoplasmosis infection. Acyclovir’s oral half-life is 1.5-2.5 hours. 9-CMMG, a water-soluble acyclovir metabolite, can penetrate cerebrospinal fluid, hence feasible to create a neurotoxic impact in a brain defect patient, yet the cellular mechanism remains unknown. Acyclovir must be administered with caution to patients with brain defect because it has the potential to cause neurotoxicity.